Lesão na base e concentrações de ácido indolbutírico no enraizamento de estacas apicais de figueira ‘Roxo de Valinhos’ - Becker, Lucas Eduardo; Pio, Rafael; Campagnolo, Marcelo Angelo; Dalastra, Idiana Marina [UNESP]; Curi, Paula Nogueira; Abreu Moura, Pedro Henrique (Universidade Estadual de Londrina (UEL), 2010)
This work aimed to increase the rhizogenic potential of cuttings collected from the apical portion of the branches of fig trees, performing injuries and treating the cuttings with indolbutyric acid (IBA). Apical cuttings of 'Roxo de Valinhos' fig tree were collected in July. The cuttings were standardized with 20 cm in length and basal diameter of 10 mm. The cuttings received or not incisions at the basis (parallel cuts of 2 cm) and immersed in IBA at 0, 1000, 2000 and 3000 mg L(-1) for 10 seconds. The cuttings were buried (3/4 of the length) in moistened sand, inside a screen house (50% of light). After 60 days it was found that treatment with IBA benefits in the development of apical cuttings, and the concentration that achieved the best results was 2000 mg L(-1); the use of injury at the base of the cuttings helps rooting.
Incision at the base and concentrations of indolbutyric acid on rooting of apical cuttings of 'Roxo de Valinhos' fig tree
Keywords: Ficus carica L; propagation; IBA